Research Progress in Ionic Liquid-Based Electrolytes for Electrochromic Devices - Hao Zhang; Yixuan Liu; Xuehan Wang; Keying Feng; Qilin Wang; Zheng Chen; Zhenhua Jiang (Molecules)
Electrochromic (EC) technology has become one of the smart technologies with the most potential for development and application at this stage. Based on electrochromic devices (ECDs), this technology has shown extraordinary potential in the fields of smart windows, display devices, and sensing systems. With the optimization and iteration of various core components in ECDs, the electrolyte layer, a key component, evolved from its initial liquid state to a quasi-solid state and solid state. As driven by increasing application demands, the development trend indicates that all-solid-state, transparent electrolytes will likely become the future form of the electrolyte layer. Recently, the application of ionic liquid (IL)-based electrolytes in the field of electrochromism attracted a lot of attention due to their ability to bring outstanding EC cycling stability, thermal stability, and a wider operating voltage range to ECDs, and they are regarded as the new generation of electrolyte materials with the most potential for application. Although compared with conventional electrolytes, IL-based electrolytes have the characteristics of high price, high viscosity, and low conductivity, they are still considered the most promising electrolyte materials for applications. However, so far, there has been a lack of comprehensive analysis reports on “Research progress in ionic liquid-based electrolytes for electrochromic devices” within the EC field. In this article, the research progress of IL-based electrolytes in ECDs will be summarized from three perspectives: liquid, quasi-solid, and solid state. The future development directions of IL-based electrolytes for ECDs are discussed.